Comparative transcriptome analysis of Citrus macrophylla tree infected with Citrus tristeza virus stem pitting mutants provides new insight into the role of phloem regeneration in stem pitting disease - Khalilzadeh, Maryam; Weber, Kyle Clark; Dutt, Manjul; El-Mohtar, Choaa Amine; Levy, Amit (Frontiers in Plant Science, 2022)
Stem-pitting is a complex and economically important virus associated disease perennial woody plants. The molecular mechanisms and pathways occurring during virus-plant interaction that result in this phenomenon are still obscure. Previous studies indicated that different Citrus tristeza virus (CTV) mutants induce defined stem-pitting phenotypes ranging from mild (CTV∆p13) to severe (CTV∆p33) in Citrus macrophylla trees. In this study, we conducted comparative transcriptome analyses of C. macrophylla trees infected with CTV mutants (CTV∆p13 and CTV∆p33) and full-length virus in comparison to healthy plants as control. Mild CTV stem-pitting mutant had very few differentially expressed genes (DEGs) related to plant defense mechanism and plant growth & development. In contrast, substantial gene expression changes were observed in plants infected with severe mutant and full-length virus, indicating both p13 and p33 proteins of CTV acted as regulator of symptom production by activating or modulating plant responses, respectively. Analysis of transcriptome data for CTV∆p33 and full-length virus suggested that xylem specification has been blocked by detecting several genes encoding xylem, cell wall and lignin degradation, and cell wall loosening enzymes. Furthermore, stem pitting was accompanied by downregulation of transcription factors involved in regulation of xylem differentiation and downregulation of some genes involved in lignin biosynthesis, showing that the xylem differentiation and specification program has been shut off. Upregulation of genes encoding transcription factors associated with phloem and cambium development indicated the activation of this program in stem pitting disease. Furthermore, we detected induction of several DEGs encoding proteins associated with cell cycle re-entry such as chromatin remodeling factors, cyclin, and histone modification. This kind of expression pattern of genes is related to xylem differentiation & specification, phloem & cambium development, and cell cycle re-entry during secondary vascular tissue (SVT) regeneration. Microscopy analysis confirmed that the regeneration of new phloem is associated with stem-pitting phenotypes. The findings of this study thus provide evidence for the association between stem-pitting phenotypes and SVT regeneration, suggesting that the expression of these genes might play important roles in the production of stem-pitting symptoms. Overall, our findings suggest that phloem regeneration contributes to the production of stem-pitting symptoms.